Values in the Kalondo Wei Tradition in the Wedding Ceremony of the Mbojo Ethnic Group in Mawu Village, Ambalawi Subdistrict, Bima Regency - Fatun Hairunnisyah; Mohamad Mustari; Sawaludin Sawaludin (JURNAL PENDIDIKAN IPS, 2025)
The erosion of local culture due to modernization has increasingly influenced the mindset and lifestyle of society, especially among the younger generation. This study explores the values in the Kalondo Wei tradition in Mawu Village and its role in strengthening the cultural identity of the Mbojo ethnic community. The research employed a descriptive qualitative approach with in-depth interviews, participatory observation, and documentation. The samples consisted of traditional leaders, religious figures, family representatives, and community members involved in the wedding procession. The findings show that each stage of the Kalondo Wei procession—preparation, escort, parade, and celebration—contains noble values reflecting the principles of Pancasila. These include values of divinity, socio-cultural harmony, mutual cooperation, and the development of moral and mental strength. Kalondo Wei functions not only as a cultural ritual but also as a medium for transmitting values and character education to the younger generation. This research contributes to the preservation of local culture amidst the challenges of globalization.